2023
DOI: 10.1139/cjz-2022-0190
|View full text |Cite
|
Sign up to set email alerts
|

Differences in thermal energetics of the cave myotis (Myotis velifer) from a cool and a warm environment of central Mexico

Abstract: Endotherm homeotherms deal with the energetic cost of maintaining a stable body temperature (Tb) in ecosystems differing in ambient temperature (Ta). In response, animals adjust some of their thermal energetics to meet the energy requirements of thermoregulation. Bats are small mammals with a geographical distribution that may include environments with different Ta. Therefore, these animals should adjust their thermal energetics depending on the environmental characteristics of the habitats where they live. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…For instance, Bozinovic et al (2014) found that, for 85 species of rodents, the species inhabiting cold climates presented a wider TNZ b than those living in warm climates. Similarly, Medina-Bello et al (2023) found that individuals of the cave myotis ( M. velifer ) from a warm tropical dry forest had a narrower TNZ b than bats from a temperate forest. Although differences in climate affinity may explain the lack of relationship between M b and TNZ b , this topic needs further investigation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…For instance, Bozinovic et al (2014) found that, for 85 species of rodents, the species inhabiting cold climates presented a wider TNZ b than those living in warm climates. Similarly, Medina-Bello et al (2023) found that individuals of the cave myotis ( M. velifer ) from a warm tropical dry forest had a narrower TNZ b than bats from a temperate forest. Although differences in climate affinity may explain the lack of relationship between M b and TNZ b , this topic needs further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…We placed one empty chamber of the same size (410 mL) inside the cabinet to take simultaneous baseline measurements from the animal chamber every second. Because we did not have any system that allowed us to switch the airflow between the empty chamber and the animal’s chamber to the same respirometer, we followed the protocol used by Medina-Bello et al (2023) to take the baseline measurements in our experiments. In this methodology, the empty chamber was connected to a different respirometer of the same brand (FoxBox®, Sable Systems International, Las Vegas Nevada, U.S.A.) with the same type of sensors (O 2 fuel cell and CO 2 infra-red sensors) and the same flow rate as that of the experimental chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most bat species have an optimal roost type and inter-individual spacing, which varies based on aggression, body size, air temperature, and other factors. Many species use darker spaces in the cave that are further from the entrance of the roost, and larger or more aggressive species may be more likely to have more space between individuals to reduce stress and the possibility of overheating (Medina-Bello et al, 2023;Rodrigues et al, 2003). Multiple variables can influence the well-being of roosting bats, including the structure of the roosts, the surrounding ecological conditions and anthropogenic interventions within cave ecosystems (Nagy & Postawa, 2011;Sedlock et al, 2014).…”
Section: Introductionmentioning
confidence: 99%